Interleukin-6 role in the severity of COVID-19 and intensive care unit stay length - Taher Al barzin, Ruqaya Muhammed Ghareeb; Ghafour Raheem, Shler; Khudhur, Pinar Khalid; Abdulkarimi, Rahim; Mohammadnejad, Esmaeil; Tabatabaee, Amir (Cellular and Molecular Biology, 2020)
Evaluation of cytokine production in COVIID-19 disease, in which the cytokine storm is one of the most important pathological features in complicated cases, especially interleukin 6 as a pre-inflammatory cytokine that exacerbates the immune response, could help determine the pathophysiology of the disease. Examining the level of this cytokine along with other related factors can help to better understand the pathogenesis of this disease. In this cross-sectional study, 48 patients with COVID-19 whose disease was confirmed by swap testing were evaluated. The demographic information of the individuals, the symptoms of the disease, and the ward in which they were admitted were recorded. Blood samples were taken from patients to test for interleukin-6 levels by electrochemiluminescence immunoassay (ECLIA, Roche Diagnostics). Due to the lack of specific treatment protocols for patients and the use of supportive treatments based on meeting the nutritional needs for all patients, blood albumin levels and nutritional status of patients were also evaluated using Subjective Global Assessment (SGA) Form. Their calorie intake was assessed by calculating the number of calories received based on the type of nutrition and compared to the required amount calculated through the Harris-Benedict equation. 48 laboratory-confirmed 2019-nCoV infected patients were included in the study with the mean age of 46.4 ± 8.3 years. 21 patients were admitted to the intensive care unit (ICU). There was no significant difference between the ICU admitted and patients admitted inward in terms of demographic characteristics, and history of previous diseases (p > 0.05). The average interleukin 6 (IL-6) in patients was 72.3±34.4 pg/ml. ICU admitted patients had higher IL6 levels (p=0.001). The mean interleukin 6 level was 89.04±34.1 pg/ml in patients admitted for less than 7 days and it was significantly higher (119.2±28.3) in patients hospitalized for more than 7 days (p=0.001). there was no significant difference in terms of nutritional status and albumin level between ICU admitted and ward admitted patients (p >0.05). Our study shows that there may be possible associations of IL6 and disease severity and ICU stay length.